Determinants of Net Profit Margin in Plastic and Packaging Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2020-2022 Period - Saputra, Pijai Opin; Nurdiawansyah, Nurdiawansyah; Aminah, Aminah (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Net profit margin is important to be able to increase company profits. Net profit margin is a comparison that shows the company's net profit on the results of buying and selling, the higher the value of the net profit margin the higher the organization's ability to earn net profit from sales. The purpose of this study is to understand and measure the impact of Current Ratio (CR) and Debt to Asset Ratio (DER) on net profit margin for plastic and packaging sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. This study used a quantitative approach with a total of 36 research samples. The sample selection technique uses purposive sampling. The test was conducted using multiple regression analysis, research data obtained through financial reports sourced on the Indonesia Stock Exchange. Liquidity as measured by CR does not significantly affect net profit margin. While another factor is that leverage measured by DER has a significant positive impact on net profit margin. The limitations of this study are the lack of samples and the low adjusted R square number of 0.439, meaning that the independent variable is only able to describe its effect on the dependent variable as much as 43.9%. Suggestions for future research are to add samples and other variables including (1) company size; (2) sales growth; (3) total asset turnover and so on that can explain the effect on net profit margin.